Strategi Pengembangan Bisnis Keripik Pisang - anjasuari, nur; Suhaeni, Suhaeni; Nur’azkiya, Luthfi (Jurnal Ilmiah Wahana Pendidikan, 2024)
PT Bayou Berjaya Indonesia is a producer that processes original banana chips into various flavored banana chips in Kota Baru District, Karawang Regency. This study aims to analyze the amount of added value, the main internal and external factors, and business development strategies. The method used was survey. The data collected were primary data and secondary data. Primary data was obtained by interviews and questionnaires with 7 respondents. Secondary data were obtained from the Central Bureau of Statistics, previous research journals, and books. The sampling method is purposive sampling. Data analysis was carried out qualitatively and quantitatively. Data processing using the Hayami method, IFAS matrix, EFAS matrix, IE matrix, and SWOT matrix. The results of the study are the added value obtained of Rp169,333.33/kg or 69.17% greater than 40% which means the value is high. The most influential internal and external factors are product purchases through market places and quality products, limited financial resources and semi-modern production equipment, increasingly widespread cooperation in product marketing, and product damage in the distribution process. Alternative strategies suggested are increasing product promotion on social media, expanding product marketing with traditional retail and modern retail, increasing product legality such as BPOM, and adding information on packaging related to Nutrition facts and product value explanations.